GPU Rendering of Relief Mapped Conical Frusta - Bhagvat, D.; Jeschke, S.; Cline, D.; Wonka, P. (Computer graphics forum, 2009)
This paper proposes to use relief‐mapped conical frusta (cones cut by planes) to skin skeletal objects. Based on this representation, current programmable graphics hardware can perform the rendering with only minimal communication between the CPU and GPU. A consistent definition of conical frusta including texture parametrization and a continuous surface normal is provided. Rendering is performed by analytical ray casting of the relief‐mapped frusta directly on the GPU. We demonstrate both static and animated objects rendered using our technique and compare to polygonal renderings of similar quality.